Enhanced Lipase Production in Pichia pastoris via Multiple Copies of Bacterial Lipase Genes and Co-expression of the HAC1 Gene - Puspitasari, Esti; Rustam, Yepy Hardi; Satya, Andreas Adhi; Suwanto, Antonius; Wahyudi, Aris Tri; Astuti, Rika Indri (Bogor Agricultural University, Indonesia, 2026)
The hac1 gene, a key regulator of the untranslated protein response (UPR), was co-expressed in Pichia pastoris GS115 to enhance the production of a lipase from Geobacillus stearothermophilus. Multicopy lipase constructs (1X and 4X) were transformed with pPICZAwbe_hac1, generating GS115/T1.2RQ(1X)_hac1 and GS115/T1.2RQ(4X)_hac1 strains. The GS115/T1.2RQ(1X)_hac1 strain showed an 186% lipase activity after 120 hours versus the control (100%), while the GS115/T1.2RQ(4X)_hac1 strain showed a faster initial increase (38% at 48 hours) and 28% at 120 hours, which was beneficial for efficient enzyme production. Overexpression of the hac1 gene enhances lipase production because it activates UPR genes when the endoplasmic reticulum is stressed due to a large number of recombinant proteins and forms proteins that are not appropriately folded. SDS-PAGE and tributyrin plate assays confirmed extracellular lipase expression ( 43 kDa). These results demonstrate that hac1 co-expression significantly (p = 0.01) enhances lipase production in Pichia pastoris, especially in lower-copy constructs. This is the first report of co-expressing hac1 with Geobacillus stearothermophilus lipase genes in yeast. The findings are expected to contribute to developing more efficient microbial cell factories for producing industrial enzymes.